Autophagic cell death - Baehrecke, Eric (Henry Stewart Talks, 2007)
Morphological forms of cell death, Why is autophagy of interest to cell death researchers?, What is autophagy?, Discovery of autophagy genes, How is autophagy regulated?, Class I PI3K signalling and Class III PI3K signalling, Ubiquitin-like conjugation systems, Where has autophagic cell death been observed?, What are the possible roles of autophagy in dying cells?, Evidence in support of autophagy prolonging cell survival, Studies in flies and mammals suggest that both autophagy and caspases can be involved in cell death of the same cell, Evidence in support of autophagy promoting cell death, Inhibition of caspase-8 promotes autophagic cell death of L929 cells by autophagic degradation of catalase